Exploration and local forecast of gold-ore deposits based on typomorphic properties of pyrite - Pshenichkin, Anatoliy Yakovlevich; Ananyev, Yuri Sergeyevich; Bushmanov, Aleksey Ivanovich; Abramova, Raisa Nikolaevna (IOP Publishing, 2015)
The article describes the data in exploration and local forecast of gold-ore deposits based on typomorphic pyrite properties. The pyrite properties: crystal shape, impurity-elements and thermal EMF change in relation to the deposit formation conditions are consistent with the mineralogical and geochemical zoning of ore bodies and deposits. In this case, it is possible to evaluate the ore zone erosion, prospectivity and productivity of the ore bodies at depth and flanks. Mineralogical sampling on pyrite and gold should be conducted on the basis of other methods during exploration and mining.
Keywords: разведка; локальный прогноз; золоторудные месторождения; типоморфные свойства; пириты